2022
DOI: 10.1126/sciadv.abq0952
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition mechanism of NKCC1 involves the carboxyl terminus and long-range conformational coupling

Abstract: The Na-K-2Cl cotransporter-1 (NKCC1) is an electroneutral Na + -dependent transporter responsible for simultaneously translocating Na + , K + , and Cl − ions into cells. In human tissue, NKCC1 plays a critical role in regulating cytoplasmic volume, fluid intake, chloride homeostasis, and cell polarity. Here, we report four structures of human NKCC1 (hNKCC1), both in the absence and presence of loop diuretic (bumetan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Here, we found that these hydrophobic interactions involved Ala 414, Val 417, Val 418 and Leu 421 from TM 4, while Phe 659, Leu 663 and Ile 666 from TM 9 (Figure ). These interactions, statically present also in the cryo-EM structures, were stably maintained during our equilibrium MD simulations, in both the IO and OO states. In addition, we observed the crucial involvement of TM 10, which was key to the NKCC1’s rocking-bundle mechanism in our simulations.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Here, we found that these hydrophobic interactions involved Ala 414, Val 417, Val 418 and Leu 421 from TM 4, while Phe 659, Leu 663 and Ile 666 from TM 9 (Figure ). These interactions, statically present also in the cryo-EM structures, were stably maintained during our equilibrium MD simulations, in both the IO and OO states. In addition, we observed the crucial involvement of TM 10, which was key to the NKCC1’s rocking-bundle mechanism in our simulations.…”
Section: Resultsmentioning
confidence: 64%
“…Interestingly, the hydration level of the outer vestibule in the OO state was significantly affected by the Arg 307–Glu 389 salt bridge (Figure S8). It is also worth noting that the drug bumetanide is bound to the outer vestibule in all the available cryo-EM structures of NKCC1 in the OO state. , Ligand binding at the outer vestibule hampers the formation of the Arg 307-Glu 389 salt bridge, which is, therefore, proven to be crucial for the rocking-bundle mechanism in NKCC1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative analysis of this latter BUM binding mode to the outward-facing NKCC1 ( Figure S13, Table S8 ) shows that BUM in this binding pose exhibits a binding free energy comparable to that obtained in this study. In addition, while we were revising the manuscript, a new structure of the human NKCC1 was released showing yet another possible binding site of the loop diuretics located in the intracellularly-exposed C-terminal domain [ 43 ]. This new finding supports the proposition that BUM can cross the cell membrane and bind to NKCC1 from the cytosolic side and suggests that the loop diuretic binding modes/mechanism are perhaps more intricate than originally envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…Like the Na–K–2Cl cotransporter [5], the K–Cl cotransporter functional unit is a dimer [6]. The recent cryo-electron microscopy (cryo-EM) structures of NKCC1 [7 ▪▪ ,8 ▪ ], KCC1–KCC4 [9 ▪▪ ,10,11] confirms the dimeric nature of the transporters. As cells express multiple K–Cl cotransporters [12–14], it is believed that they likely express heterodimers.…”
Section: Introductionmentioning
confidence: 87%